Pengembangan Manajemen Mutu Pendidikan Islam Menuju Era Society 5.0 - Ishak Ishak; Siti Patimah; Andi Warisno; Nurul Hidayati Murtafiah (Journal on Education, 2024)
This examination expects to make sense of the execution of value the board in Islamic schooling towards the time of society 5.0. The examination completed is field research. The examination was directed at Pondok Pesantren Muzammil al Aziziyah Aceh Tenggara . The examination results show that the educational program executed at this Lembaga pendidikan alludes to the 2013 educational plan which is centered around dominance and utilization of science and information. Taking into account its status as a religion-based school, Pondok Pesantren Muzammil al Aziziyah Aceh Tenggara likewise stresses the legalism side or perspective as an additional worth in evaluating the nature of madrasas by the local area and government. Notwithstanding, in executing realizing, all subjects use pointers adjusted from a blend of industry 4.0 and society 5.0 result ideas, in particular: initiative; computerized education; correspondences; the capacity to understand people on a deeper level; business venture; worldwide citizenship; critical thinking; collaboration; and strict. This marker was taken by thinking about that in the event that later on there are requests for parts of society 5.0, Lembaga pendidikan s don't have to make changes. As such, this pointer doesn't create issues from here on out.